On periglacial morphodynamics in the Aleutian Islands, SW-Alaska - Schunke, Ekkehard (ERDKUNDE, 1999)
Based on field work in the Aleutian Island of Unalaska during the summers of 1996 and 1997, the paper deals with the effect of a highly oceanic frost climate on periglacial geomorphology. The periglacial features of Unalaska Island consist essentially of forms of frost-weathering, gelifluction, micro-scale ground patterning, of surface flattening, deflation, nivation, slush-flow action, and of fluvial morphodynamics. The occurence and distribution of periglacial phenomena indicate specific altitudinal differentiations, the lowland of subpolar grassland (up to about 150 m a.s.l.) not showing morphodynamic effects of freezing action. Complementary measurements of basic climatic and hydrologic parameters in the high oceanic milieu of Unalaska Island show that the numerous pluvial discharge events during summer cause only limited fluvial action: the main valley formation is produced essentially during the snow-melt period. Finally, the periglacial geomorphological and frost-climatological position of the Aleutian Islands within the periglacial zone of the American-European Arctic and Subarctic, with its variation between highly continental to highly oceanic conditions, shows: the Aleutian Islands differ strongly from the continental periglacial regions (1) through a rather small variability of their periglacial features and (2) through minor frequencies, densities, and sizes of periglacial forms. The reason is mainly the relatively small intensity, duration, and depth of seasonal ground freezing.